Pandemi dalam Tafsir Sufi: Dialektika Trilogi Sufistik ‘Abd al-Qādir al-Jīlānī, Ibn ‘Arabī dan Achmad Asrori al-Ishaqi - Chafid Wahyudi; Ainul Yaqin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
The pandemic has reignited longstanding tensions between science and religion, transforming their once harmonious relationship into an intense conflict. This discord has cast a shadow on the credibility of religion in the midst of the pandemic and the evolution of scientific civilization. This study presents a religious discourse through the Sufi trilogy of ‘Abd al-Qādir al-Jīlānī, Ibn ‘Arabī, and Achmad Asrori al-Ishaqi. Within this interpretative framework, al-Jīlānī suggests the pandemic symbolizes destiny and human misbehavior consequences. Ibn ‘Arabiī views it as part of the Absolute phenomenon, while al-Ishaqi sees it as a reflection of an unfriendly human-nature relationship. This exploration aims to provide nuanced insights, transcending binary conflicts, and fostering a comprehensive understanding of the challenges posed by the pandemic within the context of science and religion integration.